The geology and hydrogeology of springs on Cape Breton Island, Nova Scotia, Canada: an overview - Baechler, Fred E.; Cross, Heather J.; Baechler, Lynn (Atlantic Geoscience Society, 2019)
Cape Breton Island springs have historically played a role in developing potable water supplies, enhancing salmonid streams, creating thin-skinned debris flows, as well as mineral and hydrocarbon exploration. Cape Breton Island provides a hydrogeological view into the roots of an ancient mountain range, now exhumed, deglaciated and tectonically inactive. Exhumation and glaciation over approximately 140 Ma since the Cretaceous are of particular relevance to spring formation. A total of 510 springs have been identified and discussed in terms of hydrological regions, flow, temperature, sphere of influence, total dissolved solids, pH and water typing. Examples are provided detailing characteristics of springs associated with faults, karst, salt diapirs, rockfall/alluvial systems and debris avalanche sites. Preliminary findings from a monitoring program of 27 springs are discussed. Future research should focus on identifying additional springs and characterizing associated groundwater dependent ecosystems. Incorporating springs into the provincial groundwater observation well monitoring program could facilitate early warning of drought conditions and other impacts associated with changing climate.